A simple parsimony-based approach to assess ancestor-descendant relationships - Aubert, D. (Український ботанічний журнал, 2017)
One of the main goals of systematics is to reconstruct the tree of life. Half a century ago, the breakthrough of cladistics was a major step towards this objective because it allowed us to assess relatedness patterns among species, an abstract kind of relationship. Unfortunately, the philosophy of cladism forbade to go further and to seek more realistic relationships, like the ancestor-descendant relationship, which is the expected fundamental kind of relationship of the tree of life according to Darwinian evolution. Here, I describe a simple parsimony-based procedure which can be used to transform a classical cladogram into a genuine phylogenetic tree, i.e. a caulogram. It consists in deleting as many unobserved and unnamed nodes as possible and replacing them with observed and named species. A new Bayesian non-stochastic weighting scheme is used to assess character reliability for both this procedure and classical cladogram construction. I illustrate the whole process by assessing the relationships between the species of the moss genus Didymodon sensu lato (Pottiaceae) and discuss the resulting caulogram by confronting it with the previous methodology from the evolutionary literature. I finally argue that strictly adhering to cladist epistemology is untenable and that we must seek new formal methods to find ancestral species as well as ancestral higher taxa. Однією з головних цілей систематики є реконструкція Дерева життя. Півстоліття тому проривом стала кладистика, яка виявилась важливим кроком на шляху до цієї мети, що дозволив нам визначити зв'язки спорідненості між видами, абстрактний вид спорідненості. На жаль, філософія кладизму не дозволила просунутися далі в пошуку більш реальних взаємозв'язків, таких як зв'язок предок-нащадок, який, відповідно до дарвінівської еволюційної концепції, ймовірно, є основним типом зв'язків на Дереві життя. У статті описана проста методика на основі парсимоніі, яка може бути використана для перетворення класичної кладограми у справжнє філогенетичне дерево, тобто в каулограму. Ця методика полягає у видаленні якомога більшого числа неспостережених і неіменованих вузлів та в їх заміні реально визначеними та іменованими видами. Як в цій методиці, так і при побудові класичної кладограми, для оцінки надійності ознаки використовується нова байєсівська нестохастична схема зважування. Для ілюстрації проводиться оцінка взаємозв'язків між видами мохів роду Didymodon sensu lato (Pottiaceae) з обговоренням отриманої каулограми шляхом її співставлення з попередньою методологією відповідно до еволюційних публікацій. На закінчення робиться висновок про недоцільність суворого додержання кладистичної епістемології та необхідність пошуку нових формальних методів для встановлення предкових видів, а також і предкових таксонів вищих рангів. Одной из главных целей систематики является реконструкция Древа жизни. Полвека тому назад прорывом стала кладистика, которая оказалась важным шагом на пути к этой цели, позволившим нам оценить относительные родственные связи между видами, абстрактный тип родства. К сожалению, философия кладизма не позволила продвинуться дальше в поиске более реальных родственных взаимосвязей, таких как связь предок-потомок, которая, согласно дарвинистской эволюционной концепции, является, очевидно, основополагающим типом связей на Древе жизни. В статье описана простая методика на основе парсимонии, которая может быть использована для преобразования классической кладограммы в настоящее филогенетическое дерево, то есть в каулограмму. Эта методика состоит в удалении как можно большего числа ненаблюдаемых и неименованных узлов и в замене их наблюдаемыми и именованными видами. Как в этой методике, так и при построении классической кладограммы, для оценки надежности признака используется новая байесовская нестохастическая схема взвешивания. В качестве иллюстрации проводится оценка взаимосвязей между видами мхов рода Didymodon sensu lato (Pottiaceae) с обсуждением итоговой каулограммы путем сопоставления ее с ранее применявшейся методологией по материалам эволюционных публикаций. В заключение делается вывод о несостоятельности строгого следования кладистической эпистемологии и необходимости поиска новых формальных методов для установления предковых видов, а также предковых таксонов более высоких рангов.